Estudo para o desenvolvimento de metodologia eletroanalítica na determinação de 17α-metiltestosterona - Mendonça , Raul Xavier de (2018)
The 17α-methyltestosterone used to masculinize shrimp, nile, tilapia and other fish, from genetically female to male phenotypicall the it is a hormone that acts on the endocrine system and accumulates progressively at trophic levels. Public agencies do not have legislation in force for it control, making it necessary to control this hormone in the environment. Due to the scarcity of electroanalytical methods, the determination of this hormone was studied with the use of sodium nitroprusside, potassium permanganate with bismuth electrodes and graphite paste of voltammetric techniques. Using a nujol and graphite electrode, the analyte was determined by complexation with nitroprusside, observing a potential peak at 430 mV. With the use of potassium permanganate it was noticed the consumption of the permanganate ion in 176 mV, confirmed with the aid of UVVis spectrophotometry